A community based cross sectional study on morbidities and social problems among geriatric population - Jairaj, Sangeetha; Palabindela, Ramesh; D., Sridhar (International Journal Of Community Medicine And Public Health, 2019)
Background: In India, in the last one and half decades longevity of the people has increased due to decline in mortality rate, better medical and health care facilities and improvements in overall quality of life of people. Presently India has the second largest geriatric population in the globe. In 2001, geriatric population was 77 million in India and it is estimated that in India total number of elderly will rise to 150 million by 2025 and by the year 2050 the number would rise to about 324 million.4 Methods: A community based cross sectional study was conducted in an urban slum located in Secunderabad. Almost 225 subjects more than 60 years were included in study after giving oral consent. People with severe morbidity and unable to give consent were excluded from study. Results: Majority (70%) of the resident experienced verbal abuse followed by physical abuse (13%) at least one time. About 11% felt they were being neglected by their family members. Daughter-in-law was the major person involved in the elder abuse accounting for 45.9%, followed by son 24.3%. Abuse from relatives accounted for 21.6%. Spouse and daughter were involved in elder abuse in about 5.4% and 2.7% cases respectively. Conclusions: As recently said by Financial Minister in Parliament of India, old age population growing drastically in India, especially in south India. Increasing geriatric population leading to increase in need of health care and psychological assistance.